PEDAGOGICAL ACTIVITY "FIRST STATE THEATER FOR CHILDREN": ANALYSIS OF ARCHIVAL MATERIALS 1920-1927 YEARS - М.А. Derhach (Academy of Cognitive and Natural Sciences, 2022)
Pedagogical activity of "The First State Theatre for Children "Fairy-tale"": analysis of archives materials 1920-1927. The process o f the creation and developing of the first theatre for children in Ukraine is revealed in the report. Pedagogical influence of the theatre on children revealed in 20-th years of the XX the century. The recovered facts determined key-directions of pedagogical work of the theatres in the following years.